Penguapan Pelarut dari Tetesan Ekstrak dalam Pengering Sembur (Solvent Evaporation from Drops of Natural Dye Extract in Spray Drier) - Rahayuningsih, Edia; Rahayu, Suprihastuti Sri; Sasita, Ester; Rahayu, Ginanjar Pamuji; Abriyanto, Abriyanto; Pambudi, Pambudi (Fakultas Teknik, 2006)
The main objective of this research umbrella is to minimize the weakness of usage of natural dye solution. In this step, the studies were emphazied on evaluating the mass transfer parameters from solvent to dry air in spray drier and developing an empirical correlation that corellates between mass transfer cofficient and any pertinent variables. The experiment was conducted by dropping extract solution from the top of a glass column, while dry air was flown counter-currently. By counting the number of drops and measuring the volume of the solution, therefore the diameters of drops could be determined. The amount of solvent evaporated was determined by weighing the solution that was collected at the bottom of the column. The experiments were carried out at a similar condition for various level position of drop inputs (20 cm, 40, cm, 60 cm, 80 cm, 100 cm, and 120cm).The effective diffusivity and interface mass transfer coefficient were evaluated by curve fitting method between data of solvent content in extract solution and calculated solvent content in extract solution in any posistion. In order to generalize the empirical correlation between the interface mass transfer coefficient and the affecting variables, the experiments were performed for various air flow velocity and raw materials. Based on the simulation results of Model I and Model II, it could be concluded that solvent diffusion rate in the drop and interface mass transfer rate have an important role in the drying process. The coefficient of diffusion rate of solvent (water) in extract drops of katuk leaf mangosteen fruit seal, and kesumba are 0.012 cm2/s; 0.0143 cm2/s; and 0.0131 cm2/s respectively, meanwhile the ethanol diffusivity in curcumine drop is 0.0122 cm2/s.. The empirical correlation between the interface mass transfer coefficient and the affecting variables can be expressed in the following equation: